Perceptions of medical students toward teledermatology as an educational tool: a cross-sectional study - Ureña-Paniego, Clara; Soto-Moreno, Alberto; Montero-Vílchez, Trinidad; Martínez-López, Antonio; Buendía-Eisman, Agustín; Arias-Santiago, Salvador (Frontiers in Medicine, 2023)
Introduction: Teledermatology consultations have recently been on the rise, especially due to the SARS-COV-2 pandemic. The role of Teledermatology has been extensively discussed as a mean for the education of dermatology residents. Nevertheless, little has been explored on its use as a pedagogical tool for medical students. The objectives of this study were to assess the level of satisfaction of medical students with Teledermatology and to evaluate their opinion about its use as an educational tool. Methods: A cross-sectional study was carried out at the Dermatology Department, Hospital Universitario Virgen de las Nieves, Granada (Spain). Participants were fourth-year medical students. Every student would spend half of their internship in face-to-face consultations and the other half in teledermatology consultations. Data was collected via self-administered questionnaires. Results: 81 students were finally surveyed, being 66.67% (73/81) female. A majority of students considered a mixed clinical internship model (face-to-face consultations combined with teledermatology) more suitable for dermatology learning (p= 0.49) and for obtaining higher marks (p=0.04). Nevertheless, face-to-face practice was considered more useful for their training as general practitioners (p=0.04). Conclusion: Despite the fact that students highly value doctor-patient relationship, teledermatology is considered a powerful educational tool.